Correlation patterns prevalence, and co-occurrence of ergot alkaloids in cool-season adapted cereal grains revealed with molecular spectroscopy and LC-MS/MS equipped HPLC system. (1st November 2022) - Shi, Haitao; Yu, Peiqiang
Graphical abstract: Highlights: LC-Tandem-MS equipped HPLC System was applied to determine correlation patterns of ergot alkaloids (EAs) Individual EAs was positively correlated in cool-season adapted cereal grain. Strong correlation pattern were detected between individual EAs and total EAs. High correlation patterns prevalence and co-occurrence of EAs show a high threat. Abstract: It is necessary to obtain more recent data on the prevalence and co-occurrence of mycotoxins in feed and food to minimize risks. This study examined the recent presence, co-occurrence, and correlation patterns of six major ergot alkaloids (EAs; i.e. ergocornine, ergocristine, ergocryptine, ergometrine, ergosine, and ergotamine) in cool-season adapted barley (n = 57) and wheat (n = 80) submitted by livestock producers and industries for testing ergot alkaloids/mycotoxins by liquid chromatography − tandem mass spectrometry method. Overall, 91% industry-submitted barley samples and 84% industry-submitted wheat samples tested positive for at least one ergot alkaloid and 33% industry-submitted barley and 38% industry-submitted wheat samples were found to be co-contaminated with all six major EAs. The content of total EAs in 9 industry-submitted barley (16%) and 18 industry-submitted wheat (23%) samples exceeded the recommended maximum allowable level for lactating or pregnant animals (250 ppb). All the barley and wheat samples that contained detectable ergosine were found to co-occur with other EAs. Overall, the content of individual EAs was positively correlated with each other and strong correlations ( r  > 0.8, P  < 0.01) were detected between the content of individual EAs and total EAs. These results implied that the industry and producers submitted cool-season adapted barley and wheat samples contaminated with a single EA is likely to contain high levels of other major EAs. The patterns of individual EAs in this study were distinct from previous studies that focus on samples from European countries. Ergocristine was remained as the predominant EAs in the industry-submitted cool-season adapted barley and wheat samples at levels up to 9438.8 and 12416.2 ppb, respectively. While the mean contents of ergosine were the lowest (68.5 and 50.6 ppb for the industry-submitted cool-season adapted barley and wheat samples, respectively). The high prevalence and co-occurrence of EAs indicated that ergot contamination is still posing a significant threat to food and feed industry and more research is expected to reduce the contamination level and explore the toxicological significance of various co-occurrence profiles. A full scale of investigation for all barley and wheat samples is needed to obtain a full picture of mycotoxin contamination.